(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2009)
My purpose in submitting this article is to give a comprehensive description of the work which I carried out for the Human Education Programme, a presentation for which I gave at the IIPE (International Institute of Peace Education) Conference heldat the University of Haifa in Israel at the end of July and beginning of August 2008. Thus the following report seeks to give a description of a UNESCO schools cooperation network health education programme which took place and was entitled: “Human rights education and children’s rights - Though different, girls are equal to boys”, conducted at Marasleio second experimental state primary school in Athens, Greece. This project has been conducted during the last two successive academic years among a group of twenty-four Year Three primary school pupils from Greece in 2006-07 and in 2007-08, among twenty-three Year Four primary school pupils from Greece and for a period of five weeks, nineteen Year Four primary school pupils from Germany via e-twinning. The programme has been a combination of projects comprising “Health Education” and “Human Rights Education” respectively, and has taken place over a period of four months during each of the last two academic years.